2021
DOI: 10.1093/eurheartj/ehab724.3040
|View full text |Cite
|
Sign up to set email alerts
|

Automated processing of thermal imaging to detect COVID-19 and microvascular dysfunction

Abstract: Background Coronavirus disease 2019 (COVID-19) is associated with microvascular dysfunction. Non-invasive thermal imaging can hypothetically detect changes in perfusion, inflammation and vascular injury. We sought to develop a new point-of-care, non-contact thermal imaging tool to detect COVID-19 by microvascular dysfunction, based on image processing algorithms and machine learning analysis. Materials and methods We captured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A recent study from our lab has shown that thermal imaging during graded aerobic exercise stress tests, combined with advanced image processing, is correlated with exercise intensity and pulmonary ventilation [7]. Advanced image processing algorithms are also used to measure other parameters, such as temperature distribution [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from our lab has shown that thermal imaging during graded aerobic exercise stress tests, combined with advanced image processing, is correlated with exercise intensity and pulmonary ventilation [7]. Advanced image processing algorithms are also used to measure other parameters, such as temperature distribution [7][8][9].…”
Section: Introductionmentioning
confidence: 99%